AIM AND MEANING OF BREATHING EXERCISES: INTERDISCIPLINARY LITERATURE REVIEW - Steinmane, Valerija; Fernate, Andra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Respiration is an indispensable aspect of life that significantly influences both the physical and mental well-being of individuals, depending on such factors as depth and rhythm. Exploring the distinctions between chest and abdominal breathing is crucial for understanding their profound impacts, and embracing appropriate breathing exercises has proven to be advantageous for short-term relief and long-term holistic health. While acknowledged for diverse therapeutic applications, such as mitigating vocal cord fatigue, a comprehensive exploration of breathing exercises remains essential. Sport scientists and coaches are encouraged to acquire a set of breathing exercises for future implementation in the training routines. This study strives to conduct an interdisciplinary literature review to shed light on the aims, meaning, and classification of breathing exercises. Employing a literature review methodology, were analysed peer-reviewed articles from PubMed and ScienceDirect published during the years from 2000 to 2023, focusing on such keywords as breathing exercises, deep breathing, nasal breathing, abdominal breathing, thoracic breathing, pursed-lip breathing, breathing control, and respiratory muscle training. The research findings illustrate the multifaceted definitions, components, aims, and classifications of breathing exercises. This study establishes a foundation for identifying distinct subtypes, contributing to a more nuanced understanding of the significance and purpose of breathing exercises in enhancing overall well-being.